TRANSFORMATION OF TRADITIONAL SETTLEMENTS AND DISASTER VULNERABILITY - Maha Putra, I Nyoman Gede (Journal of Architectural Research and Education, 2020)
As a setting of life and cultural products made by humans, settlements always undergo transformation along with the dynamics of their inhabitants’ lives. The dynamics of occupants, in addition to being impacted by the development of local knowledge, changes in the way humans respond to climate, and cultural transformation, are also influenced by external factors. External factors that influence settlement transformation can arise in the form of urbanisation, changes in social and political systems, economics, and technological development. In traditional societies, natural threats are predictable and conquerable. The transformation of settlements can take place in the same frame, promoting natural considerations, or in a different frame with the existence of new ideas and knowledge and technology coming from the outside. To be able to understand the transformation of traditional settlements and their transformations in relation to disaster vulnerability, this paper evaluated the causing factors, patterns, and consequences resulted from the transformation of settlements. For this reason, urban morphological studies are applied as an evaluation method. The results of the evaluation of settlement transformations reveal that traditional settlements are farther away leaving natural-harmony patterns at the root of their existence. Economic approach has replaced the cosmological-based settlement. It is recommended that natural site characteristic should be taken into consideration in order to avoid natural disaster in the future. This means that the traditional approach is still relevant in contemporary situation.Keywords: Traditional settlements; transformation; disaster vulnerablity